PENGARUH METODE COOPERATIVE LEARNING TERHADAP HASIL BELAJAR PAI SISWA KELAS VIII DI SMP IT MTA KARANGANYAR - Hidayati, Fariha; Hidayah, Nur; Rochmawan, Alfian Eko (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This study's objectives are to: (1) determine how cooperative learning techniques are used with eighth-grade students studying Islamic Education (PAI) at SMP IT MTA Karanganyar; (2) evaluate the students' learning outcomes in the PAI subject at SMP IT MTA Karanganyar; and (3) examine the impact of cooperative learning techniques on the students' learning outcomes. This research uses a correlational strategy in conjunction with a quantitative method. 59 students' answers to questionnaires and documents were used to get the data. The hypothesis was tested using the product moment correlation data analysis technique. The findings showed that: (1) the use of cooperative learning techniques was moderate, totaling 80%; (2) the learning outcomes of the students in the PAI subject were also moderate, totaling 61%; and (3) there is a significant impact of the use of cooperative learning techniques on the learning outcomes of the students in the PAI subject, as demonstrated by a strong correlation with a r square value of 0.867.